2014
DOI: 10.1111/1574-6941.12406
|View full text |Cite
|
Sign up to set email alerts
|

Isolation ofSphaerotilus-Leptothrixstrains from iron bacteria communities in Tierra del Fuego wetlands

Abstract: Sheath-forming iron- and manganese-depositing bacteria belonging to the Sphaerotilus-Leptothrix group (SLG) are widespread in natural and artificial water systems. Known requirements for their growth include the presence of organic substrates and molecular oxygen. High concentrations of reduced iron or manganese, although not necessary for most species, make their growth a noticeable phenomenon. Such microbial communities have been studied mostly in the Northern Hemisphere. Here, we present descriptions of div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…After an incubation time of up to 2 weeks at room temperature, we selected dark brown colonies that formed on the agar surface. Iron- and manganese-deposition of the strain was confirmed using the methods of Schmidt et al (4). EDX mapping of colonies suggested that manganese and iron were predominantly concentrated outside the bacteria cells.…”
Section: Genome Announcementmentioning
confidence: 99%
“…After an incubation time of up to 2 weeks at room temperature, we selected dark brown colonies that formed on the agar surface. Iron- and manganese-deposition of the strain was confirmed using the methods of Schmidt et al (4). EDX mapping of colonies suggested that manganese and iron were predominantly concentrated outside the bacteria cells.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Strain A 288, which originated from an iron and manganese-depositing biofilm of the Lower Oder Valley National Park, was isolated and cultivated as described elsewhere ( 8 ). The iron-depositing ability of the strain, which formed dark, brown-colored colonies on iron- and manganese-containing media, was confirmed according to Schmidt et al ( 8 ). Genomic DNA was extracted using the GeneMATRIX soil DNA purification kit (Roboklon, Berlin, Germany).…”
Section: Genome Announcementmentioning
confidence: 99%
“…Sequential dilutions of sampled ochrous material were spread on modified Leptothrix medium ( 10 ) (deionized water was replaced by sterile well water), and reddish-brown colonies were selected after incubation for 17 to 21 days at room temperature. The iron- and manganese-depositing activity of the isolate was verified by dissolving the colonies with oxalic acid (10%) as previously described by Schmidt et al ( 11 ). Strain R_RK_3 is a small Gram-negative bacterium with a coccus shape of 2- to 4-µm length and a width of 1.0 µm.…”
Section: Genome Announcementmentioning
confidence: 99%